A proposal of excipients mixture for the elaboration of Na131I capsules - Alviar M. (2020)
The authors are grateful for the financial support of the Fondo Nacional de Desarrollo Cient?fico Tecnol?gico y de Innovaci?n (FONDECYT) and to the staff of Analytical Techniques Laboratory and the Radioisotope Production Plant for their contributions.